(untitled) (Homoeopathy for All, 2024)
Addiction or substance dependence or neuropsychiatric disorders are characterized by the desire to take more drugs despite the mild problems that occur. It is a problem that affects people’s brain and behaviour , leading to the inability to control the use of legal or illegal drugs. Substances such as alcohol, marijuana and nicotine are also considered drugs. In the case of drug addiction, homeopathic remedies can be effective in relieving symptoms and preventing addiction.